Kuantan food map (mobile application) - Nurul Hafizah Ayunni, Yusop (2014)
Various types of food map application was developed till today. The used is to help in searching for food place easily. This application, named Kuantan Food Map will help user to find for food place in Kuantan. It works by navigating user to the food place chosen. There are few functions providing by Kuantan Food Map in order to filter user's searching area. In order to develop this application, food places; stalls, restaurants and food courts data in Kuantan are recorded. Data are including the locations, menus as well as the atmosphere of the place. The data are recorded based on oberservation method. The output will display map with navigation function to guide user to the chosen food place. This application will reduce user's time in searching for food place to go for in Kuantan.